Techno-Economic evaluation of an evacuated tube solar air collector with inserted baffles. (August 2021) - Veera Kumar, A; Arjunan, TV; Seenivasan, D; Venkatramanan, R; Vijayan, S
Evacuated tube solar collectors exhibit excellent performance even in poor insolation periods and are highly preferred for low as well as for medium temperature applications. In this study, an evacuated tube with inserted baffle solar air collector (ETIBSAC) was developed to investigate the effect of mass flow rate of air on energy, exergy, enviro-economic characteristics. The results revealed that the maximum outlet air temperature was observed during the peak irradiance period as 80.5 °C and the system is capable of delivering hot air above 50 °C between 9:30 am to 4:00 pm in clear sky days at the mass flow rate 100 kg/h. The maximum thermal efficiency of 55.4% was achieved at the mass flow rate of 500 kg/h. The highest exergy efficiency of 2.7% was recorded at 100 kg/h and diminishes with increasing mass flow rate of air due to more exergy destruction. The cost per kWh to deliver the hot air in the range of 60 to 70 °C is estimated as 0.00027 (0.02 INR) at the mass flow rate of 100 kg/h. It is concluded that the developed air collector can be efficiently used for process heating applications.